Handbook of mindfulness : theory, research, and practice - Brown, Kirk Warren; Creswell, J. David; Ryan, Richard M. (Guilford Press, 2015)
"While we have learned a great deal about mindfulness in the past 30 years, unquestionably the field of mindfulness science is still maturing, and in the chapters herein the authors have taken pains to point out how the current research is limited in its methods and conclusions, and have pointed to specific ways in which future research studies can overcome these limitations. That said, the work represented in this Handbook is among the best conducted to date, measured in terms of scientific creativity, sophistication, and insight. Our hope is that this volume offers readers both a panoramic view of the current science of mindfulness and a compass to help guide its ongoing evolution"--